Principles of macroeconomics - Taylor, John B. (Boston : Houghton Mifflin, 1995)
Economics
Keywords: Macroeconomics; Economic interaction; Supply; Demand model; Employment; Unemployment; Investment; Economic growth; Monetary system; Inflation; Fiscal policy; Monetary policy; International trade; Trade policy; International finance; Global macroeconomic policies; Market economies